Advancing services for adult ADHD: the development of the ADHD Star as a framework for multidisciplinary interventions - Marios Adamou; Katharine Graham; Joy MacKeith; Sara Burns; Lisa-Marie Emerson (BMC, 2016)
Abstract Background Attention Deficit Hyperactivity Disorder is prevalent in adulthood, resulting in serious impairment across multiple domains of living. Despite clinical guidance recommendations, the relative infancy of research on service provision for adults with ADHD, along with the evidence transfer gap, means that there is a lack of specific frameworks for service delivery. Igniting research and developing service delivery frameworks within adult ADHD is an essential step in the provision of effective services for adults with ADHD. Method Following the methodology used in previous related research that utilises a Participatory Action Research approach, we gathered data from clinicians and service users on the domains of living in which they wish to create change, and the steps and end point of the change process. This data was utilised, alongside data gathered from previous research and policies, to develop the domains of assessment for the ADHD Star, and the scale on which change is assessed. Results The resulting tool, the ADHD Star, consists of eight domains: understanding your ADHD, focus and attention, organising yourself, friends and social life, thinking and reacting, physical health, how you feel and meaningful use of time. Each domain is rated on a five-point scale, the 'ladder of change', ranging from 'stuck' to 'choice'. Conclusions The ADHD Star offers a guiding framework for the development of care pathways and subsequent service provision for adults with ADHD, based on multi-disciplinary, holistic and person-centred care.